The new home : a handbook for tenants (London : The Health and Cleanliness Council, 1937)
1937 1937 1930s 24 pages : illustrations SHOES SHOULD BE WELL POLISHED AS SOON AS THEY ARE TAKEN OFF AND ARE DRY Shoe-trees or clean crumpled paper should be pushed into the toes to keep the shape. Polish not only improves the appearance and lengthens shoe-life, but also makes leather waterproof. DRY CLOTHES IN THE OPEN AIR Fresh air is clean and wholesome and gives the best colour to the washing, but on foggy or wet days it is necessary to dry indoors. Old-fashioned houses had racks which could be slung up to the ceiling. To-day you are more likely to find a hot cupboard, warmed by water pipes. Remove any dry linen airing there, then put damp clothes in the cupboard to dry. Do not store an electric iron in a hot cupboard; it is not good for the flex. If, connected with your houses or block of flats, there is a laundry, it is better to use it for washing your clothes than to do the washing in the home. CLEAN CLOTHES ARE ESSENTIAL FOR HEALTH Let your wash-day equipment be as up-to-date as possible. An electric wash-boiler will enable you to do your washing more quickly and more easily. The whole family should have clean underclothes at least once a week, and the baby should have them more frequently. Clean overalls help the housewife to keep herself dainty during working hours. Use the Municipal Wash House if there is one in your neighbourhood and you cannot do your washing easily at home. Bed-linen should be as spotlessly clean as body-linen. The electric wash-boiler is an excellent blanket-washer and it abolishes the drudgery of washing by the old-fashioned method. With an electric iron, sheets and pillow-cases can easily be made to look as if they were professionally laundered. [insert] The Council's Booklet, "Hints for the Busy Housewife," has many good wash-day wrinkles. Send 1½d. stamp. [illustration] An electric wash-boiler. 17 177/5/8/2